STUDY THE LEVELS OF PERCEPTION OF STRESS AND FORCE STATES OF LOWER, AFTER AN INTERVENTION OF ATRAINING IN PHYSICALAND PSYCHOLOGICALDANCERS. (Fiep Bulletin - online, 2013)
The physical and psychological training when work integrating body and mind, considering the individual as a whole. Objective: To examine whether there is any significant difference between levels of stress and strength of lower limbs in pre-and post-test, after an intervention by a physical and psychological training in dancers. Methodology: The sample consisted of 11 jazz dancers, of both sexes, aged between 18 and 23, members of a dance company from the city of Curitiba-PR. To collect the data testing of Vertical Thrust to assess the strength and Inventory Scale Stress Understood were applied before and after the training. The training had duration of 7 weeks. For the processing of the data analysis, a descriptive statistics (mean and standard deviation) was used, a MANOVA at a level of significance p
Keywords: Stress; Strenght; Dancers